Perlindungan Hukum Terhadap Korban Pengancaman Melalui Media Elektronik (Studi Kasus Revenge Porn) - Bertram Beryl Hanni Arrafi; Mesha Sabila Hakim; Raidah Hazirah; Nasywa Nabilla Putri A; Michaella Anandita; Jeanette Dwisca Oktaviani; Larasati (Jurnal Kewarganegaraan, 2024)
Revenge porn, or the distribution of sexual content without the victim's consent, is a form of gender-based violence that exploits digital technology. This act is often accompanied by threats and aims to humiliate the victim. This article seeks to analyze the legal protection available for victims of revenge porn in Indonesia, evaluate the existing regulations, and provide recommendations to enhance the effectiveness of legal safeguards. The analysis reveals that the current legal framework, such as the Information and Electronic Transactions Law (UU ITE) and the Pornography Law, falls short in optimally protecting victims, particularly due to ambiguous interpretations in its implementation. Comprehensive solutions, including victim-focused legal reforms, public education, and training for law enforcement officers, are urgently needed to address this issue effectively. Keyword: Revenge porn, electronic threats, legal protection, online gender-based violence, privacy rights